The Role of The United Nations in Promoting Conflict Resolution in The Escalation of Intrastate Mali Conflict Instability (2018- 2022) - Alvela Salsabilah Putri; Akim (Jurnal Hubungan Internasional, 2023)
The instability of the conflict in Mali has increased for four years since 2018. The increase in violence, military coups, political instability, humanitarian crises, and terrorism has forced the United Nations to increase its strength in pushing for the implementation of peace agreements in the Mali intrastate conflict. This research was conducted using qualitative methods with secondary data to see the role of the United Nations in encouraging the resolution of the intrastate conflict in Mali during the period of instability for the last four years. In the analysis, this study finds that through a mandate renewed every year, the United Nations adopts its role to encourage conflict resolution with the dynamics of conflicts from 2018 to 2022. Over the past four years, the role of the United Nations as an international organization to encourage the implementation of resolutions to the conflict in Mali focuses on several things, namely; (1) Overseeing Mali’s political transition, (2) Strengthening security for civilians and peacekeepers through international cooperation, (3) Acting as government assistance to promote human rights and law enforcement, and (4) Encouraging the progress of the 2015 peace agreement in Mali to achieve the maximum target. Keywords: Conflict Resolution, Intrastate Conflict, International Organization, Mali, United Nations